PENGAWASAN DINAS PERTAMBANGAN DAN ENERGI TERHADAP PERTAMBANGAN MINERAL NON LOGAM DIKABUPATEN ROKAN HULU TAHUN 2012 - Setiawan, Rian Denny; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study would like to see the role of the Dinas Pertambangan and Energy in conducting surveillance of non metallic mineral mining in Rokan Hulu in 2012. The problem is the background of this research is How the role of the Dinas Pertambangan and Energy in conducting surveillance of non metallic mineral mining in Rokan Hulu years 2012 and what are the factors that become an obstacle to the surveillance. This study is a qualitative research, the data collection techniques in this study is a descriptive analysis. This research uses documentation (observation) and interviews with key informants as information objects that aim to achieve the goal in order to get information in the study. Data used in this study is primary data and secondary data obtained through observation and interviews with key informants in this study. Based on the research and discussion that has been the writer explained in the previous chapter are based on the formulation of the problem, the authors conclude as follows.Keywords: mining, surveillance, controling